2012
DOI: 10.1083/jcb.201202005
|View full text |Cite|
|
Sign up to set email alerts
|

ADP ribosylation adapts an ER chaperone response to short-term fluctuations in unfolded protein load

Abstract: Inactivating ADP ribosylation of the ER chaperone BiP is a rapidly reversible mechanism for buffering acute changes in unfolded protein load.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
98
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(106 citation statements)
references
References 58 publications
7
98
1
Order By: Relevance
“…In the absence of stress, BiP has been shown to be a major ADP-ribosylated protein in mammalian cells 7 and is thought to be phosphorylated 8; 9 . However, whenever the load of unfolded proteins increases in the ER, the amount of modified BiP decreases 7; 911 . Accordingly, it has been suggested that the ADP-ribosylated or phosphorylated forms of BiP represent a pool of inactive oligomeric molecules that can quickly be reactivated when needed 7; 12; 13 (Fig.…”
Section: The Atpase Cycle Of Bip In the Er Environmentmentioning
confidence: 99%
See 2 more Smart Citations
“…In the absence of stress, BiP has been shown to be a major ADP-ribosylated protein in mammalian cells 7 and is thought to be phosphorylated 8; 9 . However, whenever the load of unfolded proteins increases in the ER, the amount of modified BiP decreases 7; 911 . Accordingly, it has been suggested that the ADP-ribosylated or phosphorylated forms of BiP represent a pool of inactive oligomeric molecules that can quickly be reactivated when needed 7; 12; 13 (Fig.…”
Section: The Atpase Cycle Of Bip In the Er Environmentmentioning
confidence: 99%
“…Despite this and other 1416 circumstantial evidence suggesting that BiP’s activity in vivo might be affected by post-translational modifications, it remains unclear how these modifications are controlled in response to physiological cues. Although neither the kinase nor ADP-ribosyltransferase has been identified, recently the ADP-ribosylation site of BiP was mapped to two Arg residues within its s ubstrate b inding d omain (SBD) 11 . Modification of these residues would interfere with substrate binding and thus explain earlier observations that only unmodified BiP is bound to substrates.…”
Section: The Atpase Cycle Of Bip In the Er Environmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Several post-translational modifications have been suggested to regulate BiP activities, including AMPylation [1416] and oligomerization [17]. In addition, it has been proposed that BiP is ADP-ribosylated [18, 19] and phosphorylated [19], although it has been put forward that these two postulated modifications may reflect misattributed AMPylation events [15]. …”
Section: Introductionmentioning
confidence: 99%
“…Known targets of MAR modification include the cytoskeletal proteins actin 36, 37 and desmin 38 , the protein folding chaperone GRP78 (also known as BiP) 39–42 and heterotrimeric G-proteins 4347 . Each of these proteins is MARylated on arginines instead of the canonical lysine, glutamate or aspartate residues known to be PARylated by PARPs 4850 .…”
Section: Mar Versus Parmentioning
confidence: 99%